A kind of high tear resistance and high temperature resistant organic silicon rubber and preparation method thereof
By introducing bisphenol fluorene structure into silicone rubber, the tear resistance and high temperature resistance of silicone rubber are improved, and the problem of insufficient mechanical properties of traditional silicone rubber in extreme environments is solved, and efficient application in extreme environments is achieved.
Patent Information
- Application Number
- CN202310432021.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-21
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-04-21
AI Technical Summary
Traditional silicone rubber materials have insufficient mechanical properties in oil resistance, solvent resistance, acid and alkali resistance and steam resistance, especially the tensile strength and tear strength, which limits their application in extreme environments.
By introducing a bisphenol fluorene structure into the main chain of silicon rubber, the "rigid structure" of the bisphenol fluorene ring is used to improve the stability of the group and the rigidity of the molecular chain of the silicon rubber, and enhance its mechanical properties and thermal stability.
The prepared high tear and high temperature resistant silicone rubber exhibits excellent mechanical properties and thermal stability, and can be used in extreme environments to meet the needs of aerospace and deep-sea exploration.
Smart Images

Figure HDA0004190608690000011 
Figure HDA0004190608690000021 
Figure HDA0004190608690000022
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic silicon materials, and particularly relates to a highly tear-resistant and high-temperature-resistant organic silicon rubber and a preparation method thereof. Background Art
[0002] Silicone rubber is a typical semi-inorganic and semi-organic polymer material with -Si-O- repeating structure as the main chain and organic groups such as methyl, ethyl and vinyl as the side chain. The main chain is an inorganic structure and the side chain is an organic group. It has the high temperature resistance of inorganic materials and the flexibility of organic materials. It has the advantages of high and low temperature resistance, weather resistance, low glass transition temperature, flexibility, good elasticity, electrical insulation and biocompatibility. It also has excellent properties such as wide operating temperature range, small compression permanent deformation and low cost. Therefore, silicone rubber has been widely used in industrial fields such as transportation, chemical industry, medical and health care, construction and electronic appliances, and has important applications in cutting-edge technology fields such as aviation and rockets.
[0003] Although silicon materials have many advantages and can be applied in many fields, they are still insufficient in oil resistance, solvent resistance, acid and alkali resistance, steam resistance, mechanical properties and mechanical strength, especially tensile strength and tear strength, which seriously limits their practical application. For example, under the influence of environmental factors such as pressure vessels in chemical applications, high temperature and high pressure workshops, and daily durable products, traditional silicon rubber materials cannot simultaneously meet the mechanical properties, high temperature resistance, weather resistance and tear resistance requirements of these relatively extreme environments. Therefore, it is necessary to perform certain physical and chemical modifications on silicon rubber materials to further improve their various properties.
[0004] Introducing large steric groups into the main chain of silicone rubber, shielding adjacent groups from each other, can improve the stability of the groups, inhibit cyclization degradation reactions, and improve the heat resistance of silicone rubber. Improving the performance of silicone rubber by introducing benzene rings has been widely used. Wang Yimin et al. compared the performance of diphenyl silicone rubber and monophenyl silicone rubber at different phenyl contents and found that when the performance was at the same level, the content of phenyl chain segments in diphenyl silicone rubber was lower. For example, when the tensile strength was the highest, the phenyl content of monophenyl silicone rubber was 20%, and that of diphenyl silicone rubber was 5%. Huang Yanhua et al. introduced a certain amount of large groups such as phenyl and trifluoropropyl into the side groups of silicone rubber, which could destroy the regularity of the main chain of silicone rubber and inhibit low-temperature crystallization. A 4% phenyl content could reduce the crystallization peak temperature of silicone rubber from -40°C to about -90°C, improving the low-temperature resistance of silicone rubber. Huang Yuhong et al. used lithium hydroxide as an initiator and N, N-dimethylformamide (DMF) as an accelerator to prepare polydimethyl (methylvinyl)-diphenyl-methylvinyl triblock structure silicone rubber. After vulcanization, the permanent compression deformation of the silicone rubber at room temperature was only 8.73% (16.41% for random structure silicone rubber under the same conditions). Chen Hongying et al. used liquid bisphenol A and bisphenol fluorene to introduce bisphenol fluorene structure into epoxy resin. By selecting different raw materials and different ratios, the different performance balances of bisphenol fluorene modified epoxy resin were adjusted to improve the thermal properties of the material. Wang Fang et al. used bisphenol fluorene (BHPF), bisphenol A (BPA), and 4,4-dichlorodiphenyl sulfone (DCS) as raw materials and used nucleophilic substitution method to synthesize ternary copolymer polysulfones with different BHPF contents, and prepared ternary copolymer polysulfones with number average molecular weight (Mn)>2×10 4 The terpolymer is a terpolymer of 209-254°C, and with the increase of BHPF content, the glass transition temperature (Tg) of the polymer gradually increases to 209-254°C, the main chain decomposition temperature>510°C, and when the BHPF content is 80% (molar fraction), the Tg of the material is 254°C, and the transmittance in the visible light range is 84%. It can be seen from the above invention that although the prepared phenyl-containing silicone rubber structure has good high temperature resistance, its production process is complicated, the effect of introducing phenyl into the side group is not as good as that of introducing phenyl into the main chain, and the mechanical properties are not outstanding enough. At present, there is no research on introducing bisphenol fluorene structure into silicone rubber. Silicone rubber itself has extremely outstanding high and low temperature resistance and heat resistance. The combination of the two will further promote the complementary advantages of the materials and improve the mechanical properties of silicone rubber. Summary of the invention
[0005] In order to make up for the deficiencies of the prior art, the present invention proposes a highly tear-resistant and high-temperature-resistant organic silicone rubber and a preparation method thereof, thereby improving the mechanical properties and thermal stability of the silicone rubber.
[0006] The technical solution of the present invention is:
[0007] A method for preparing a highly tear-resistant and high-temperature resistant organic silicone rubber comprises the following steps:
[0008] (1) Add dihydroxydimethylsiloxane and bisphenol fluorene into a two-necked flask, heat to 50-60° C. while stirring to mix the reactants evenly, and then remove water under vacuum for 1 hour; then heat to 120° C. and stir to react until a viscous, white gel-like substance is observed, then start cooling to 70-80° C. to obtain a polycondensation product;
[0009] (2) adding the siloxane ring body and methylvinylsiloxane into a three-necked flask, heating to 45-55° C. while stirring, mixing the reactants evenly, and then removing water in a vacuum for 1 hour; then adding the catalyst alkali glue, the capping agent and the polycondensation product obtained in step (1) into the three-necked flask and removing water in a vacuum for 1 hour; then stirring and reacting at 110° C., normal pressure and N2 protection for 2 hours;
[0010] (3) The product obtained by the reaction in step (2) is placed in a vacuum drying oven and dried at a temperature set to 170° C. The activity of the catalyst is destroyed at high temperature and decomposed into methanol. During the drying process, methanol and small molecules in the system are removed to obtain the target product.
[0011] Preferably, in step (1), the molar ratio of dihydroxydimethylsiloxane to bisphenol fluorene is 1:1.
[0012] Preferably, the preparation method of dihydroxydimethylsiloxane in step (1) is: adding dimethyldichlorosilane to concentrated sulfuric acid and hydrolyzing it to generate dihydroxydimethylsiloxane.
[0013] Preferably, the mass ratio of the siloxane ring body, methylvinylsiloxane, catalyst alkali glue, capping agent and the polycondensation product obtained in step (1) in step (2) is (8-20):1:(3-5):0.1:(10-12).
[0014] Preferably, the siloxane ring body in step (2) is any one of hexamethylcyclotrisiloxane (D3), octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), and dodecamethylcyclohexasiloxane (D6).
[0015] Preferably, the methylvinylsiloxane in step (2) is any one of tetramethyltetravinylcyclotetrasiloxane (V4), pentamethylpentavinylcyclopentasiloxane (V5), and hexamethylhexavinylcyclohexasiloxane (V6).
[0016] Preferably, the catalyst alkali gel of step (2) is prepared by placing octamethylcyclotetrasiloxane and an alkaline catalyst into a flask, heating to 45-55° C. while stirring to mix the reactants evenly, then removing water under vacuum for 1 hour, and then stirring the reaction at normal pressure and 80° C. for 2-3 hours.
[0017] The mass ratio of octamethylcyclotetrasiloxane to the alkaline catalyst is 25:1.
[0018] The alkaline catalyst is any one of potassium siloxane, potassium hydroxide, tetramethylammonium hydroxide, tetramethylsiloxane, and tetrabutylphosphosiloxane.
[0019] Preferably, the capping agent in step (2) is any one of decamethyltetrasiloxane, hexamethyldisiloxane and silane ether.
[0020] Preferably, the specific operation of vacuum dehydration is: turn on the vacuum pump control system, when the pressure reaches 0.1 MPa, vacuum dehydration is performed for 1 hour, then the vacuum pump is turned off, and nitrogen is added to bring the system into a normal pressure state.
[0021] The beneficial effects of the present invention are:
[0022] 1. The present invention introduces the "rigid structure" of bisphenol fluorene benzene ring into the main chain of the silicone rubber structure. Adjacent groups shield each other, which can improve the stability of the groups and inhibit the cyclization degradation reaction. At the same time, the rigidity of the silicone rubber molecular chain is increased, the flexibility is reduced, and the low-temperature resistance is weakened. The prepared silicone rubber has excellent mechanical properties and thermal stability.
[0023] 2. The structure of the present invention is novel, the performance is excellent, the preparation process is simple, and the use is convenient. The material prepared by the present invention can be used in extreme environments and meet the application requirements of aerospace, deep sea exploration and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A synthetic route map for highly tear-resistant and high-temperature resistant silicone rubber;
[0025] Figure 2 This is a comparison chart of the tear strength of the silicone rubber samples prepared in Examples 1-7 and Comparative Examples 1-4;
[0026] Figure 3 A comparison chart of the tensile strength of the silicone rubber samples prepared in Examples 1-7 and Comparative Examples 1-4;
[0027] Figure 4 A comparison chart of the elongation at break of the silicone rubber samples prepared in Examples 1-7 and Comparative Examples 1-4;
[0028] Figure 5 This is the infrared spectrum of the silicone rubber prepared in Example 1;
[0029] Figure 6 This is a thermogravimetric analysis diagram of the organic silicone rubber prepared in Example 1;
[0030] Figure 7It is a comparison chart of the 5% thermal decomposition temperature and the residual carbon rate of the silicone rubber samples prepared in Examples 1-7 and Comparative Examples 1-4. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] (1) Add 5g of dimethyldichlorosilane to 20ml of industrial 98% sulfuric acid to hydrolyze to generate dihydroxydimethylsiloxane. Weigh 4.6g of dihydroxydimethylsiloxane and 17.5g of bisphenol fluorene into a two-necked flask, heat to 55°C while stirring to mix the reactants evenly, and then remove water in vacuum for 1h. Then heat to 120°C and continue stirring. Stop stirring when a viscous, white gel-like substance is observed, and cool to 75°C to obtain a polycondensation product.
[0034] (2) Place 15 g of octamethylcyclotetrasiloxane and 0.6 g of potassium siloxane in a flask equipped with a nitrogen tube, a stirring magnet, a condenser and a thermometer. Heat to 47°C while stirring to mix the reactants evenly, and then remove water in vacuo for 1 hour. Then heat the reaction system to 80°C and stir the reaction for 2.5 hours to obtain a transparent, viscous, highly active catalyst alkali gel.
[0035] (3) Add 60g of octamethylcyclotetrasiloxane and 5g of tetramethyltetravinylcyclotetrasiloxane into a three-necked flask equipped with a nitrogen tube, a mechanical stirring blade, a condenser tube and a thermometer. Heat to 48°C while stirring to mix the reactants evenly, and then remove water in a vacuum for 1 hour. Then add the catalyst alkali glue, decamethyltetrasiloxane and the condensation product obtained in step (1) into the three-necked flask and remove water in a vacuum for 1 hour. Then stir and react for 2 hours at normal pressure, 110°C and N2 protection. The mass ratio of octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, catalyst alkali glue, decamethyltetrasiloxane and condensation product is 12:1:3:0.1:10.
[0036] Figure 5 This is the infrared spectrum of silicone rubber. It can be seen that 1440cm -1 and 2910cm -1 The left and right sides are the characteristic peaks of -CH2, 1000-1130cm -1 The strong absorption band that appears is the characteristic peak of Si-O-Si, 890cm -1 、1060cm -1 and 1210cm -1The left and right are the characteristic peaks of Si-R, 890cm -1 It is the characteristic peak of the para-disubstituted benzene ring. The appearance of the above characteristic peaks indicates the successful introduction of the bisphenol fluorene benzene ring structure and the successful synthesis of high-tear and high-temperature resistant silicone rubber.
[0037] The prepared silicone rubber was cured by adding a crosslinking agent and then tested according to ASTM D882 at a test speed of 500 mm / min. Figure 2-4 shown.
[0038] The prepared silicone rubber was tested using a TG209 F3 thermogravimetric analyzer. The test results are as follows: Figure 6-7 shown.
[0039] Example 2
[0040] (1) Add 5g of dimethyldichlorosilane to 20ml of industrial 98% sulfuric acid to hydrolyze to generate dihydroxydimethylsiloxane. Weigh 4.6g of dihydroxydimethylsiloxane and 17.5g of bisphenol fluorene into a two-necked flask, heat to 55°C while stirring to mix the reactants evenly, and then remove water in vacuum for 1h. Then heat to 120°C and continue stirring. Stop stirring when a viscous, white gel-like substance is observed, and cool to 75°C to obtain a polycondensation product.
[0041] (2) Place 15 g of octamethylcyclotetrasiloxane and 0.6 g of potassium siloxane in a flask equipped with a nitrogen tube, a stirring magnet, a condenser and a thermometer. Heat to 47°C while stirring to mix the reactants evenly, and then remove water in vacuo for 1 hour. Then heat the reaction system to 80°C and stir the reaction for 2.5 hours to obtain a transparent, viscous, highly active catalyst alkali gel.
[0042] (3) Add 80g of octamethylcyclotetrasiloxane and 5g of tetramethyltetravinylcyclotetrasiloxane into a three-necked flask equipped with a nitrogen tube, a mechanical stirring paddle, a condenser tube and a thermometer. Heat to 48°C while stirring to mix the reactants evenly, and then remove water in a vacuum for 1 hour. Then add the catalyst alkali glue, decamethyltetrasiloxane and the condensation product obtained in step (1) into the three-necked flask and remove water in a vacuum for 1 hour. Then stir and react for 2 hours at normal pressure, 110°C and N2 protection. The mass ratio of octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, catalyst alkali glue, decamethyltetrasiloxane and condensation product is 16:1:5:0.1:12.
[0043] Example 3
[0044] (1) Add 5g of dimethyldichlorosilane to 20ml of industrial 98% sulfuric acid to hydrolyze to generate dihydroxydimethylsiloxane. Weigh 4.6g of dihydroxydimethylsiloxane and 17.5g of bisphenol fluorene into a two-necked flask, heat to 55°C while stirring to mix the reactants evenly, and then remove water in vacuum for 1h. Then heat to 120°C and continue stirring. Stop stirring when a viscous, white gel-like substance is observed, and cool to 75°C to obtain a polycondensation product.
[0045] (2) Place 15 g of octamethylcyclotetrasiloxane and 0.6 g of potassium siloxane in a flask equipped with a nitrogen tube, a stirring magnet, a condenser and a thermometer. Heat to 47°C while stirring to mix the reactants evenly, and then remove water in vacuo for 1 hour. Then heat the reaction system to 80°C and stir the reaction for 2.5 hours to obtain a transparent, viscous, highly active catalyst alkali gel.
[0046] (3) Add 40g of octamethylcyclotetrasiloxane and 5g of tetramethyltetravinylcyclotetrasiloxane to a three-necked flask equipped with a nitrogen tube, a mechanical stirring paddle, a condenser tube and a thermometer. Heat to 48°C while stirring to mix the reactants evenly, and then remove water in a vacuum for 1 hour. Then add the catalyst alkali glue, decamethyltetrasiloxane and the condensation product obtained in step (1) to the three-necked flask and remove water in a vacuum for 1 hour. Then stir and react for 2 hours at normal pressure, 110°C and N2 protection. The mass ratio of octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, catalyst alkali glue, decamethyltetrasiloxane and condensation product is 8:1:5:0.1:10.
[0047] Example 4
[0048] (1) Add 5g of dimethyldichlorosilane to 20ml of industrial 98% sulfuric acid to hydrolyze to generate dihydroxydimethylsiloxane. Weigh 4.6g of dihydroxydimethylsiloxane and 17.5g of bisphenol fluorene into a two-necked flask, heat to 55°C while stirring to mix the reactants evenly, and then remove water in vacuum for 1h. Then heat to 120°C and continue stirring. Stop stirring when a viscous, white gel-like substance is observed, and cool to 75°C to obtain a polycondensation product.
[0049] (2) Place 15 g of octamethylcyclotetrasiloxane and 0.6 g of potassium siloxane in a flask equipped with a nitrogen tube, a stirring magnet, a condenser and a thermometer. Heat to 47°C while stirring to mix the reactants evenly, and then remove water in vacuo for 1 hour. Then heat the reaction system to 80°C and stir the reaction for 2.5 hours to obtain a transparent, viscous, highly active catalyst alkali gel.
[0050] (3) Add 60g of octamethylcyclotetrasiloxane and 3g of tetramethyltetravinylcyclotetrasiloxane into a three-necked flask equipped with a nitrogen tube, a mechanical stirring blade, a condenser tube and a thermometer. Heat to 48°C while stirring to mix the reactants evenly, and then remove water in a vacuum for 1 hour. Then add the catalyst alkali glue, decamethyltetrasiloxane and the condensation product obtained in step (1) into the three-necked flask and remove water in a vacuum for 1 hour. Then stir and react for 2 hours at normal pressure, 110°C and N2 protection. The mass ratio of octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, catalyst alkali glue, decamethyltetrasiloxane and condensation product is 20:1:3:0.1:12.
[0051] Example 5
[0052] (1) Add 5g of dimethyldichlorosilane to 20ml of industrial 98% sulfuric acid to hydrolyze to generate dihydroxydimethylsiloxane. Weigh 4.6g of dihydroxydimethylsiloxane and 17.5g of bisphenol fluorene into a two-necked flask, heat to 55°C while stirring to mix the reactants evenly, and then remove water in vacuum for 1h. Then heat to 120°C and continue stirring. Stop stirring when a viscous, white gel-like substance is observed, and cool to 75°C to obtain a polycondensation product.
[0053] (2) Place 15 g of octamethylcyclotetrasiloxane and 0.6 g of potassium siloxane in a flask equipped with a nitrogen tube, a stirring magnet, a condenser and a thermometer. Heat to 47°C while stirring to mix the reactants evenly, and then remove water in vacuo for 1 hour. Then heat the reaction system to 80°C and stir the reaction for 2.5 hours to obtain a transparent, viscous, highly active catalyst alkali gel.
[0054] (3) Add 60g of octamethylcyclotetrasiloxane and 5g of pentamethylpentavinylcyclopentasiloxane into a three-necked flask equipped with a nitrogen tube, a mechanical stirring blade, a condenser tube and a thermometer. Heat to 48°C while stirring to mix the reactants evenly, and then remove water in a vacuum for 1 hour. Then add the catalyst alkali glue, decamethyltetrasiloxane and the polycondensation product obtained in step (1) into the three-necked flask and remove water in a vacuum for 1 hour. Then stir and react for 2 hours at normal pressure, 110°C and N2 protection. The mass ratio of octamethylcyclotetrasiloxane, pentamethylpentavinylcyclopentasiloxane, catalyst alkali glue, decamethyltetrasiloxane and polycondensation product is 12:1:3:0.1:10.
[0055] Example 6
[0056] (1) Add 5g of dimethyldichlorosilane to 20ml of industrial 98% sulfuric acid to hydrolyze to generate dihydroxydimethylsiloxane. Weigh 4.6g of dihydroxydimethylsiloxane and 17.5g of bisphenol fluorene into a two-necked flask, heat to 55°C while stirring to mix the reactants evenly, and then remove water in vacuum for 1h. Then heat to 120°C and continue stirring. Stop stirring when a viscous, white gel-like substance is observed, and cool to 75°C to obtain a polycondensation product.
[0057] (2) Place 15 g of octamethylcyclotetrasiloxane and 0.6 g of potassium siloxane in a flask equipped with a nitrogen tube, a stirring magnet, a condenser and a thermometer. Heat to 47°C while stirring to mix the reactants evenly, and then remove water in vacuo for 1 hour. Then heat the reaction system to 80°C and stir the reaction for 2.5 hours to obtain a transparent, viscous, highly active catalyst alkali gel.
[0058] (3) Add 60g of hexamethylcyclotrisiloxane and 5g of tetramethyltetravinylcyclotetrasiloxane into a three-necked flask equipped with a nitrogen tube, a mechanical stirring blade, a condenser tube and a thermometer. Heat to 48°C while stirring to mix the reactants evenly, and then remove water in a vacuum for 1 hour. Then add the catalyst alkali glue, decamethyltetrasiloxane and the condensation product obtained in step (1) into the three-necked flask and remove water in a vacuum for 1 hour. Then stir and react for 2 hours at normal pressure, 110°C and N2 protection. The mass ratio of hexamethylcyclotrisiloxane, tetramethyltetravinylcyclotetrasiloxane, catalyst alkali glue, decamethyltetrasiloxane and condensation product is 12:1:5:0.1:12.
[0059] Example 7
[0060] (1) Add 5g of dimethyldichlorosilane to 20ml of industrial 98% sulfuric acid to hydrolyze to generate dihydroxydimethylsiloxane. Weigh 4.6g of dihydroxydimethylsiloxane and 17.5g of bisphenol fluorene into a two-necked flask, heat to 55°C while stirring to mix the reactants evenly, and then remove water in vacuum for 1h. Then heat to 120°C and continue stirring. Stop stirring when a viscous, white gel-like substance is observed, and cool to 75°C to obtain a polycondensation product.
[0061] (2) Place 15 g of octamethylcyclotetrasiloxane and 0.6 g of potassium siloxane in a flask equipped with a nitrogen tube, a stirring magnet, a condenser and a thermometer. Heat to 47°C while stirring to mix the reactants evenly, and then remove water in vacuo for 1 hour. Then heat the reaction system to 80°C and stir the reaction for 2.5 hours to obtain a transparent, viscous, highly active catalyst alkali gel.
[0062] (3) Add 60g of hexamethylcyclotrisiloxane and 5g of pentamethylpentavinylcyclopentasiloxane into a three-necked flask equipped with a nitrogen tube, a mechanical stirring blade, a condenser tube and a thermometer. Heat to 48°C while stirring to mix the reactants evenly, and then remove water in a vacuum for 1 hour. Then add the catalyst alkali glue, decamethyltetrasiloxane and the polycondensation product obtained in step (1) into the three-necked flask and remove water in a vacuum for 1 hour. Then stir and react for 2 hours at normal pressure, 110°C and N2 protection. The mass ratio of hexamethylcyclotrisiloxane, pentamethylpentavinylcyclopentasiloxane, catalyst alkali glue, decamethyltetrasiloxane and polycondensation product is 12:1:4:0.1:12.
[0063] Comparative Example 1
[0064] (1) Place 15 g of octamethylcyclotetrasiloxane and 0.6 g of potassium siloxane in a flask equipped with a nitrogen tube, a stirring magnet, a condenser and a thermometer. Heat to 47°C while stirring to mix the reactants evenly, and then remove water in vacuo for 1 hour. Then heat the reaction system to 80°C and stir the reaction for 2.5 hours to obtain a transparent, viscous, highly active catalyst alkali gel.
[0065] (2) Add 60g of octamethylcyclotetrasiloxane and 5g of tetramethyltetravinylcyclotetrasiloxane to a three-necked flask equipped with a nitrogen tube, a mechanical stirring paddle, a condenser tube and a thermometer. Heat to 48°C while stirring to mix the reactants evenly, and then remove water in a vacuum for 1 hour. Then add the catalyst alkali glue and decamethyltetrasiloxane to the three-necked flask and remove water in a vacuum for 1 hour. Then stir and react for 2 hours at normal pressure, 110°C and N2 protection. The mass ratio of octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, catalyst alkali glue and decamethyltetrasiloxane is 12:1:3:0.1.
[0066] Comparative Example 2
[0067] (1) Add 5g of dimethyldichlorosilane to 20ml of industrial 98% sulfuric acid to hydrolyze to form dihydroxydimethylsiloxane. Weigh 4.6g of dihydroxydimethylsiloxane and 5.5g of hydroquinone into a two-necked flask, heat to 55°C while stirring to mix the reactants evenly, and then remove water in vacuum for 1h. Then heat to 120°C and continue stirring. Stop stirring when a viscous, white gel-like substance is observed, and cool to 75°C to obtain a polycondensation product.
[0068] (2) Place 15 g of octamethylcyclotetrasiloxane and 0.6 g of potassium siloxane in a flask equipped with a nitrogen tube, a stirring magnet, a condenser and a thermometer. Heat to 47°C while stirring to mix the reactants evenly, and then remove water in vacuo for 1 hour. Then heat the reaction system to 80°C and stir the reaction for 2.5 hours to obtain a transparent, viscous, highly active catalyst alkali gel.
[0069] (3) Add 60g of octamethylcyclotetrasiloxane and 5g of tetramethyltetravinylcyclotetrasiloxane into a three-necked flask equipped with a nitrogen tube, a mechanical stirring blade, a condenser tube and a thermometer. Heat to 48°C while stirring to mix the reactants evenly, and then remove water in a vacuum for 1 hour. Then add the catalyst alkali glue, decamethyltetrasiloxane and the condensation product obtained in step (1) into the three-necked flask and remove water in a vacuum for 1 hour. Then stir and react for 2 hours at normal pressure, 110°C and N2 protection. The mass ratio of octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, catalyst alkali glue, decamethyltetrasiloxane and condensation product is 12:1:3:0.1:10.
[0070] Comparative Example 3
[0071] (1) Add 5g of dimethyldichlorosilane to 20ml of industrial 98% sulfuric acid to hydrolyze to produce dihydroxydimethylsiloxane. Weigh 4.6g of dihydroxydimethylsiloxane and 8g of 2,7-dihydroxynaphthalene into a two-necked flask, heat to 55°C while stirring to mix the reactants evenly, and then remove water in vacuo for 1h. Then heat to 120°C and continue stirring. Stop stirring when a viscous, white gel-like substance is observed, and cool to 75°C to obtain a polycondensation product.
[0072] (2) Place 15 g of octamethylcyclotetrasiloxane and 0.6 g of potassium siloxane in a flask equipped with a nitrogen tube, a stirring magnet, a condenser and a thermometer. Heat to 47°C while stirring to mix the reactants evenly, and then remove water in vacuo for 1 hour. Then heat the reaction system to 80°C and stir the reaction for 2.5 hours to obtain a transparent, viscous, highly active catalyst alkali gel.
[0073] (3) Add 60g of octamethylcyclotetrasiloxane and 5g of tetramethyltetravinylcyclotetrasiloxane into a three-necked flask equipped with a nitrogen tube, a mechanical stirring blade, a condenser tube and a thermometer. Heat to 48°C while stirring to mix the reactants evenly, and then remove water in a vacuum for 1 hour. Then add the catalyst alkali glue, decamethyltetrasiloxane and the condensation product obtained in step (1) into the three-necked flask and remove water in a vacuum for 1 hour. Then stir and react for 2 hours at normal pressure, 110°C and N2 protection. The mass ratio of octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, catalyst alkali glue, decamethyltetrasiloxane and condensation product is 12:1:3:0.1:10.
[0074] Comparative Example 4
[0075] (1) Add 5g of dimethyldichlorosilane to 20ml of industrial 98% sulfuric acid to hydrolyze to produce dihydroxydimethylsiloxane. Weigh 4.6g of dihydroxydimethylsiloxane and 30g of bisphenol fluorene into a two-necked flask, heat to 55°C while stirring to mix the reactants evenly, and then remove water in vacuum for 1h. Then heat to 120°C and continue stirring. Stop stirring when a viscous, white gel-like substance is observed, and cool to 75°C to obtain a polycondensation product.
[0076] (2) Place 15 g of octamethylcyclotetrasiloxane and 0.6 g of potassium siloxane in a flask equipped with a nitrogen tube, a stirring magnet, a condenser and a thermometer. Heat to 47°C while stirring to mix the reactants evenly, and then remove water in vacuo for 1 hour. Then heat the reaction system to 80°C and stir the reaction for 2.5 hours to obtain a transparent, viscous, highly active catalyst alkali gel.
[0077] (3) Add 60g of octamethylcyclotetrasiloxane and 5g of tetramethyltetravinylcyclotetrasiloxane into a three-necked flask equipped with a nitrogen tube, a mechanical stirring blade, a condenser tube and a thermometer. Heat to 48°C while stirring to mix the reactants evenly, and then remove water in a vacuum for 1 hour. Then add the catalyst alkali glue, decamethyltetrasiloxane and the condensation product obtained in step (1) into the three-necked flask and remove water in a vacuum for 1 hour. Then stir and react for 2 hours at normal pressure, 110°C and N2 protection. The mass ratio of octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, catalyst alkali glue, decamethyltetrasiloxane and condensation product is 12:1:3:0.1:10.
Claims
1. A method for preparing a highly tear-resistant and high-temperature resistant organic silicone rubber, characterized in that: The following steps are involved: (1) Add dihydroxydimethylsiloxane and bisphenol fluorene into a two-necked flask, heat to 50-60°C while stirring, and then remove water under vacuum for 1 hour; then heat to 120°C and stir to react until a viscous, white gel-like substance is observed, then cool to 70-80°C to obtain a polycondensation product; the molar ratio of dihydroxydimethylsiloxane to bisphenol fluorene is 1:1; (2) Add the siloxane ring body and methylvinylsiloxane into a three-necked flask, heat to 45-55°C while stirring, and then remove water in vacuum for 1 hour; then add the catalyst alkali gel, the capping agent and the polycondensation product obtained in step (1) into the three-necked flask and remove water in vacuum for 1 hour; then stir and react for 2 hours at 110°C, normal pressure and N2 protection; the mass ratio of the siloxane ring body, methylvinylsiloxane, the catalyst alkali gel, the capping agent and the polycondensation product obtained in step (1) is (8-20):1:(3-5):0.1:(10-12); (3) placing the product obtained in step (2) in a vacuum drying oven and drying the product at a temperature set at 170°C; The preparation method of the catalyst alkali glue in step (2) is as follows: octamethylcyclotetrasiloxane and an alkaline catalyst are placed in a flask, heated to 45-55°C while stirring, and then dehydrated under vacuum for 1 hour, and then stirred for reaction at normal pressure and 80°C for 2-3 hours; wherein the mass ratio of octamethylcyclotetrasiloxane to the alkaline catalyst is 25:1; and the alkaline catalyst is any one of potassium siloxane, potassium hydroxide, tetramethylammonium hydroxide, tetramethylsiloxane, and tetrabutylphosphosiloxane.
2. The method for preparing a highly tear-resistant and high-temperature-resistant organic silicone rubber according to claim 1, characterized in that: The preparation method of dihydroxydimethylsiloxane in step (1) is: adding dimethyldichlorosilane to concentrated sulfuric acid and hydrolyzing it to generate dihydroxydimethylsiloxane.
3. The method for preparing a highly tear-resistant and high-temperature-resistant organic silicone rubber according to claim 1, characterized in that: The siloxane ring body in step (2) is any one of hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and dodecamethylcyclohexasiloxane.
4. The method for preparing a highly tear-resistant and high-temperature-resistant organic silicone rubber according to claim 1, characterized in that: The methylvinylsiloxane in step (2) is any one of tetramethyltetravinylcyclotetrasiloxane, pentamethylpentavinylcyclopentasiloxane and hexamethylhexavinylcyclohexasiloxane.
5. The method for preparing a highly tear-resistant and high-temperature-resistant organic silicone rubber according to claim 1, characterized in that: The capping agent in step (2) is any one of decamethyltetrasiloxane, hexamethyldisiloxane and silane ether.
6. The method for preparing a highly tear-resistant and high-temperature-resistant organic silicone rubber according to claim 1, characterized in that: The specific operation of vacuum dehydration described in steps (1)-(2) is as follows: turn on the vacuum pump control system, and when the pressure reaches 0.1 MPa, vacuum dehydration is performed for 1 hour, then the vacuum pump is turned off and nitrogen is added to bring the system to a normal pressure state.
7. A highly tear-resistant and high-temperature-resistant organic silicone rubber prepared according to the method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Composite method and solidifying method of fluorine-containing high temperature resisting organosilicon epoxy resin
CN103130982A
Vinylbenzylated phenol compound, activated ester resin, thermoset resin composition, hardened material, interlayer insulating material, and prepreg
CN106977376A
Cited By
Pressure-resistant and tear-resistant silicone rubber and preparation method thereof
CN122213697A